Antioxidant Activity of Leucaena leucocephala Lmk.de Wit. N-Hexane Fraction - Islamiyati, Ricka; Yanulia Handayani; Kadar Ismah; Gendis Purno Yudanti; Heni Setyoningsih; Sri Fitrianingsih (HM Publisher, 2023)
Antioxidants are chemical compounds that can neutralize free radical agents. These compounds work by donating electrons to achieve a stable form, thereby inhibiting the oxidative mechanisms that cause degenerative disease. Lamtoro seeds contain many active compounds that can be used as a source of natural antioxidants and antibacterials. This study aimed to determine the antioxidant effect of the n-hexane fraction of lamtoro seeds (Leucaena leucocephala Lmk. de Wit.). This study is an in vitro experimental study. The object of study was the n-hexane fraction of lamtoro seeds, where antioxidant activity was examined using the DPPH method. Analysis was performed using a UV-Vis spectrophotometer. The n-hexane fraction contained a total flavonoid content of 9.224% and had antioxidant activity with an lC50 value of 67.94 ppm. In conclusion, the n-hexane fraction of lamtoro seeds (Leucaena leucocephala Lmk.de Wit.) has strong antioxidant activity.